ARTIFICIAL INTELLIGENCE IN BANKING: TRANSFORMING BANK MANAGEMENT AND CUSTOMER EXPERIENCE (Cuestiones de Fisioterapia, 2023)
Digital banking gets great improvements on the basis of the fast growths of ICT technology, in which quick, smooth, and cost-efficient financial transactions are available. This has unlocked many more financial services, products and business opportunities. In recent times industry's most talked about topic is the Digital Banking (DB) revolution. The challenge that has been most detrimental to digital banking transformation is the idea of digital transformation being deferred as simply a technology operations initiative, whilst the primary focus should always be on your customer experience. Digital disruption has changed the standard operating procedures of transaction details and business operations. This paper explores the various ways in which artificial intelligence the banking industry to detect, prevent and manage fraud. Nothing is very assertive; traditional rule-based fraud detection systems sometimes fail to detect in real-time. Artificial intelligence AI has come to the forefront of the financial world today. The new trend of using bank AI adoption in banking uses data-driven solutions towards a more customer-centric approach. Personalization services play an increasingly crucial role in enhancing current customer engagement and attracting new customers. This research studies the applications of AI in banking and the extended benefits to customer satisfaction and overall banking management. This study aims to evaluate the effectiveness of bank-wide operations in using AI for enhanced customer satisfaction and client engagement. The document explains the use of artificial intelligence in the best possible way for multinational banks. This paper proposes a corporate-based architecture and supports digital AI innovation to assist financial institutions in providing a more personalized customer experience.